2020
DOI: 10.1021/acs.joc.0c01324
|View full text |Cite
|
Sign up to set email alerts
|

Control of Chemoselectivity of SET-Promoted Photoaddition Reactions of Fullerene C60 with α-Trimethylsilyl Group-Containing N-Alkylglycinates Yielding Aminomethyl-1,2-dihydrofullerenes or Fulleropyrrolidines

Abstract: Knowledge about factors that govern chemoselectivity is pivotal to the design of reactions that are utilized to produce complex organic substances. In the current study, single-electron transfer (SET)-promoted photoaddition reactions of fullerene C60 with both trimethylsilyl and various alkyl group-containing glycinates and ethyl N-alkyl-N-((trimethylsilyl)­methyl)­glycinates were explored to evaluate how the nature of N-alkyl substituents of glycinate substrates and reaction conditions govern the chemoselecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 77 publications
0
11
0
Order By: Relevance
“…Notably, we indicated that the efficiencies of degradation reactions can be varied by both structural features and the arene ring substitution patterns of lignin model compounds. As part of our continuing interest in developing mild and eco-friendly photochemical techniques for lignin fragmentation, in this study, we prepared dimeric β-O-4 and β-1 lignin model compounds containing varying numbers of methoxy substituents on the arene rings and carried out visible-light-mediated photocatalytic degradation reactions of these substrates using amine-functionalized fullerene-based photocatalysts (Figure ) because these fullerene-based photocatalysts can absorb a wide range of visible-light wavelengths and serve as efficient electron acceptors (see Table S1 and Figures S1 and S2). The results showed that, compared to the lignin model photodegradation mediated using common photoredox catalysts such as methylene blue (MB), rose bengal (RB), and eosin Y (EY), the photoreactions of lignin model compounds using the amine-functionalized fullerene derivatives can lead to more efficient lignin fragmentation through a pathway involving selective C α –C β bond cleavage, and in addition, the C α - hydroxyl moiety in the lignin model compounds plays a significant role in the success of the C α –C β bond cleavage reaction of lignin model substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, we indicated that the efficiencies of degradation reactions can be varied by both structural features and the arene ring substitution patterns of lignin model compounds. As part of our continuing interest in developing mild and eco-friendly photochemical techniques for lignin fragmentation, in this study, we prepared dimeric β-O-4 and β-1 lignin model compounds containing varying numbers of methoxy substituents on the arene rings and carried out visible-light-mediated photocatalytic degradation reactions of these substrates using amine-functionalized fullerene-based photocatalysts (Figure ) because these fullerene-based photocatalysts can absorb a wide range of visible-light wavelengths and serve as efficient electron acceptors (see Table S1 and Figures S1 and S2). The results showed that, compared to the lignin model photodegradation mediated using common photoredox catalysts such as methylene blue (MB), rose bengal (RB), and eosin Y (EY), the photoreactions of lignin model compounds using the amine-functionalized fullerene derivatives can lead to more efficient lignin fragmentation through a pathway involving selective C α –C β bond cleavage, and in addition, the C α - hydroxyl moiety in the lignin model compounds plays a significant role in the success of the C α –C β bond cleavage reaction of lignin model substrates.…”
Section: Introductionmentioning
confidence: 99%
“…With prepared N-phenylglycinates 14a−14j and N-phenylalaninates 15a−15e in hand, photochemical reactions of them with C 60 were performed in conditions identical to those employed in our earlier photoreaction using N-alkylglycinates. 14 Specifically, 10% EtOH−toluene (v/v) solutions containing C 60 (0.28 mmol, 1 equiv) and AAEs (0.56 mmol, 2 equiv) were irradiated for a fixed time period by a 450 W Hanovia medium pressure mercury lamp equipped with flint glass filter (>310 nm) under either a deoxygenated (N 2 -purged) or oxygenated (O 2 -purged) environment. The photolyzates were then purified to determine the resulting photoproducts.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As far as reaction efficiency and photoproduct profiles are concerned, it is noteworthy to compare the results of photoreactions using silyl-group-containing N-alkylglycinates. 14 As shown in Table 4, first, photoreactions of N-alkyl substituted glycinates 17a−17e with C 60 took place much more efficiently (i.e., a much shorter irradiation time was required to bring about high yields of photoproducts as well as the high conversion of C 60 ) than those of N-phenyl analogs. More importantly, photoreactions of 17a−17e with C 60 led to the formation of desilylated amine-incorporated fullerenes 18a−18e as sole products rather than decarboxymethylated products.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations